Assistive technology for people with special needs and its role in enriching Arabic grammar and Qur’anic studies - Abd Allah ibn Al-Husayn Ukbari as a model - Yousef A. Baker, El-Ebiary; Mohamed Aziz, Abdelmaksoud Sayed; Rusdee, Taher (2020)
Assistive technology has an important role in helping people with disabilities, so what this technology can offer goes beyond simple help limits, is that it opens up broad prospects for a new lifestyle. Those with special needs have high concerns, strong wills, solid intentions and creative minds, which Allah Almighty blessed them to encourage and satisfy their hearts. In the context of preface of the book “Nakt al-Humyān fī Nukat al-Umyān, (biographies of notable blind people, with a section on the causes of blindness)”. Its writer Khalīl ibn Aybak al-Ṣ afadī (1296 – 1363) pointed out a saying, which has high value, deep impact, and significance tribute to people with special needs, where he said: “it’s rare to see a blind man being a dull, inefficient, inactive but blind person only can be found as an intelligent, smart and genius." This research’s title is "Assistive Technology for People with Special Needs and its Role in enriching Arabic Grammar and Qur'anic Studies (Abd Allāh ibn al-Ḥusayn ʻ Ukbarī as a model)". We will address issues of people with special needs specially Abd Allāh ibn al-Ḥusayn ʻ Ukbarī as a model as he was blinded in his youth as he was hit by chickenpox. The research seeks to discuss the saying: "Although Al- ʻ Ukbarī was a handicapped person, but he had outstanding efforts and contributions in enriching Arabic grammar and Quranic studies." It (research) aims to explain the concept of assistive technology and people with special needs, also to know our duty towards them and to mention the most important and preferred effects of Al- ʻ Ukbarī. As well as clarifying the most prominent features of Al- ʻ Ukbarī 's curriculum in his grammatical works and highlighting his efforts in enriching Arabic grammar and Quranic studies.